2016
DOI: 10.4269/ajtmh.15-0540
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Ehrlichiosis in the United States: A Summary of National Surveillance of Ehrlichia chaffeensis and Ehrlichia ewingii Infections in the United States, 2008–2012

Abstract: Abstract. Human ehrlichiosis is a potentially fatal disease caused by Ehrlichia chaffeensis and Ehrlichia ewingii. Cases of ehrlichiosis are reported to Centers for Disease Control and Prevention through two national surveillance systems: Nationally Notifiable Diseases Surveillance System (NNDSS) and Case Report Forms. During 2008-2012,613 cases of E. chaffeensis infections were reported through NNDSS. The incidence rate (IR) was 3.2 cases per million person-years (PYs). The hospitalization rate (HR) was 57% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 41 publications
1
83
3
Order By: Relevance
“…During 2008-2012, cases were primarily reported from Missouri; however, cases also were reported from 10 other states within the distribution of the principal vector, the lone star tick, A. americanum (5,57) ( Figure 13). Although E. ewingii ehrlichiosis initially was reported predominantly among persons who were immunosuppressed, passive surveillance data from 2008-2012 indicated that the majority of persons (74%) with reported E. ewingii infection did not report immunosuppression (5). No fatal cases of E. ewingii ehrlichiosis have been reported.…”
Section: Ehrlichia Ewingiimentioning
confidence: 99%
See 4 more Smart Citations
“…During 2008-2012, cases were primarily reported from Missouri; however, cases also were reported from 10 other states within the distribution of the principal vector, the lone star tick, A. americanum (5,57) ( Figure 13). Although E. ewingii ehrlichiosis initially was reported predominantly among persons who were immunosuppressed, passive surveillance data from 2008-2012 indicated that the majority of persons (74%) with reported E. ewingii infection did not report immunosuppression (5). No fatal cases of E. ewingii ehrlichiosis have been reported.…”
Section: Ehrlichia Ewingiimentioning
confidence: 99%
“…Incidence generally increases with age, with the highest age-specific incidences occurring among persons aged 60-69 years (5,13,50). Case-fatality rates are highest among children aged <10 years and adults aged ≥70 years, and an increased risk for death has been documented among persons who are immunosuppressed (5,13). In areas where ehrlichiosis is endemic, the actual disease incidence is likely underrepresented in estimates that are based on passive surveillance (51)(52)(53).…”
Section: Ehrlichiaementioning
confidence: 99%
See 3 more Smart Citations